2017
DOI: 10.1111/febs.14206
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils, G‐CSF and their contribution to breast cancer metastasis

Abstract: Evidence is mounting for a role for neutrophils in breast cancer progression to metastasis. However, the role of G‐CSF in neutrophil biology in a cancer setting remains to be defined. Herein we discuss the most recent clinical and experimental evidence for neutrophils and G‐CSF in the promotion of metastasis, demonstrating a potential mechanistic link between them. Understanding this link is imperative both for the development of diagnostic tests and for therapies targeting neutrophils to improve the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 84 publications
2
80
0
1
Order By: Relevance
“…In addition, neutrophils form neutrophil extracellular traps (NETs) that stimulate migration and invasion and trap natural killer cells 25 . The pro-metastatic role of neutrophils was also recognized in human cancer patients, and a high NLR is associated with a poor prognosis 14 . The neutrophils derived from tumor-bearing mice or from cancer patients are distinct from normal neutrophils, as tumor-associated neutrophils lack immunosuppressive activity and have a higher migration capacity 26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, neutrophils form neutrophil extracellular traps (NETs) that stimulate migration and invasion and trap natural killer cells 25 . The pro-metastatic role of neutrophils was also recognized in human cancer patients, and a high NLR is associated with a poor prognosis 14 . The neutrophils derived from tumor-bearing mice or from cancer patients are distinct from normal neutrophils, as tumor-associated neutrophils lack immunosuppressive activity and have a higher migration capacity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophils derived from tumor-bearing mice or from cancer patients are distinct from normal neutrophils, as tumor-associated neutrophils lack immunosuppressive activity and have a higher migration capacity 26 . Cancer cells promote the survival and mobilization of neutrophils by secreting G-CSF 14, 27 . We showed that at least in vitro Akt1, and not Akt2, is required for the G-CSF-induced survival of neutrophils derived from tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophil function. Neutrophils have been shown to contribute to breast cancer metastasis [29][30][31] . A number of chemokines such as CXCL5, CXCL8 and CCL24 32,33 that are differentially expressed in MUC1-ST macrophages compared to M-CSF macrophages are involved in neutrophil recruitment (figure 4a).…”
Section: Muc1-st Induced Macrophages Have Distinct Functional Capabilmentioning
confidence: 99%